Latency-Aware Routing and Multidimensional Optical Resource Allocation for CF-RAN over SDM-EON - Rodrigues, Edson Adriel; Batista, Daniel Macêdo; Oliveira, Helder (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Cloud-Fog Radio Access Networks (CF-RAN) are a promising architecture to support heterogeneous 5G services with stringent latency requirements. However, efficient optical resource allocation remains a challenge under dynamic traffic conditions. This paper proposes 5GEON, a routing and multidimensional optical resource allocation algorithm for CF-RAN over Space-Division Multiplexing Elastic Optical Networks (SDM-EON). The solution jointly considers traffic classification, latency-aware offloading, and adaptive modulation. Simulation results show that 5GEON significantly reduces blocking, achieving up to three times lower bandwidth blocking ratio than a state-of-the-art baseline, while effectively prioritizing Ultra-Reliable Low-Latency Communication (URLLC) traffic.